2022
DOI: 10.6007/ijarbss/v12-i10/14951
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Waqf Performance and Governance for Public Universities in Malaysia

Abstract: Islamic philanthropy in Malaysian education system has been well rooted in religion-based traditional educational institutions. Currently, Waqf and Endowment (WAE) grow rapidly at higher education institutions as an income generation and a long-term financial sustainability initiative. The initiative is as a result of budget cut by 20 percent for public universities since 2016 and 2017 but no raise in fee is allowed. This initiative is in line to recommendation in the University Transformation Programme (UniTP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Numerous studies have shown that administering waqf property in any institution is frequently perceived as constrained by legislation including HEIs (Shaifull Anuar et al, 2019). This scenario is likely to limit the waqf institution's ability to explore and manage waqf (Sani et al, 2022). Usman & Ab Rahman (2023) highlight that the higher authority in HEIs must follow the applicable rules for waqf development, which includes submitting an application to the relevant SIRCs before adopting waqf in their institutions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous studies have shown that administering waqf property in any institution is frequently perceived as constrained by legislation including HEIs (Shaifull Anuar et al, 2019). This scenario is likely to limit the waqf institution's ability to explore and manage waqf (Sani et al, 2022). Usman & Ab Rahman (2023) highlight that the higher authority in HEIs must follow the applicable rules for waqf development, which includes submitting an application to the relevant SIRCs before adopting waqf in their institutions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among others in Malaysia, waqf institutions that were established were HUM Endowment, Kolej Universiti Islam Melaka (KUIM) Cash Waqf Fund, and UPM Dana Waqaf llmu. Educational waqf is a religious endowment that has gained popularity in Malaysian higher education, especially when private institutions enter the system (Mujani & Yaakub, 2017;Sani et al, 2022;Usman & Ab Rahman, 2023). It is vital in meeting the requirements of those who cannot afford education particularly as well as in managing and administering the operation of the Higher Education Institution.…”
Section: Introductionmentioning
confidence: 99%